2021
DOI: 10.3390/agronomy11081567
|View full text |Cite
|
Sign up to set email alerts
|

Compost Fungi Allow for Effective Dispersal of Putative PGP Bacteria

Abstract: Use of compost is a common agricultural practice. It improves soil fertility by adding nutrients and plant growth promoting (PGP) microorganisms. The role of bacterial-fungal interactions for compost-driven fertilization, however, is still poorly understood. In this study, we investigated whether putative PGP bacteria associate to and disperse along mycelia of fungal isolates. A ‘Fungal highway column system’ was used to isolate and characterize fungal—bacterial couples derived from commercial compost (C), non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…From each well-colonized compost particle, the microbiota relevant as an ecosystem service provider will proliferate and colonize the neighboring micro-and macro-aggregates, becoming an established soil or rhizospheric population. While the effect of arbuscular mycorrhizal fungal on bacterial transport and organic phosphorus mineralization of organic phosphorus or the colonization of legume roots by symbiotic dinitrogen-fixing bacteria is known [167], the effects of compost-derived fungi on the spread of other microorganisms remains poorly studied. The same applies to the factors affecting the migration of microbial cells from compost particles to soil aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…From each well-colonized compost particle, the microbiota relevant as an ecosystem service provider will proliferate and colonize the neighboring micro-and macro-aggregates, becoming an established soil or rhizospheric population. While the effect of arbuscular mycorrhizal fungal on bacterial transport and organic phosphorus mineralization of organic phosphorus or the colonization of legume roots by symbiotic dinitrogen-fixing bacteria is known [167], the effects of compost-derived fungi on the spread of other microorganisms remains poorly studied. The same applies to the factors affecting the migration of microbial cells from compost particles to soil aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…All groups of microorganisms need each other in the composting process. The most efficient composting process is achieved with mixed composting, involving both bacteria and fungi [7].…”
Section: Incrodutionmentioning
confidence: 99%
“…Interestingly, using bacterial-fungal consortiums can have a prolonged influence, a potential in the environment. González-González et al (2021) [30] showed that Aspergillus fungi present in compost or in rhizosphere soil where compost was previously applied promoted the spread of plant growth stimulating Pseudomonas and Bacillus via mycelia. This can have a positive impact on the growth and development of plants and represents a way to improve their protection against pathogens.…”
Section: Introductionmentioning
confidence: 99%